Study on Prolapsed Intervertebral Disc Cases Admitted in Military Hospitals (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: Prolapsed intervertebral disc is a condition that can occur anywhere along the spine, but most often occurs in the lower back. It is sometimes called a bulging, protruding or ruptured disc. It is one of the most common causes of lower back pain as well as leg pain or sciatica.Objective: To study the demographic characteristics of prolapsed lumbar intervertebral disc by age, gender, clinical presentation, levels of spinal column involvement, treatment options and post operative complications for lumbar disc prolapse.Materials and Methods: This cross sectional study was conducted in Rangpur and Saidpur Combined Military Hospital from September2017 to December 2018. A Total of 223 Cases was studied and data were collected by semi-structured questionnaire by face to face interview and medical documents.Results: Most commonly affected disc spaces were L5/S1(35.87%)followed by L4/L5 (33.18%) and L4/L5,L5/S1(14.28%). Males were mostly affected and commonest among 30-39 years’ age group (45.29%). Chi-square test is done and result is statistically significant (p